Association between apathy in patients with maintenance dialysis and hospitalization or mortality: a prospective cohort study - Fang, Yu; Chen, Lei; Zhang, Yueyue; Yuan, Weijie; Han, Bin (Frontiers in Psychiatry, 2023)
Background: Patients receiving maintenance dialysis experience increased rates of hospitalization and mortality. Apathy is associated with reduced quality of life and increased hospitalization, institutionalization, and death. Whether apathy contributes to poor outcomes in population undergoing maintenance dialysis remain unknown. Methods: We conducted a prospective cohort study of maintenance dialysis population who were consecutively recruited at the Dialysis Center of Shanghai General Hospital between July 2017 and August 2018 and were followed up for 3 year. Apathy status was measured by the the Apathy Evaluation Scale. The study outcomes were the occurrence of death and first hospitalization. Results: A total of 647 participants included in this study, 274 (42.3%) had a current apathy and 373 (57.7%) were not. During the follow-up period, 394 (60.9%) were hospitalized, and 169 (26.1%) died. Kaplan-Meier analysis showed that the risks of hospitalization and mortality were significantly higher in individuals with apathy than in those without apathy (both p < 0.001). Apathy at baseline was associated with hospitalization and death both in univariate analysis and in all multivariable models (all p < 0.001). Conclusions: Apathy was highly prevalent and independently correlated with an increased risk of poor outcomes in patients with maintenance dialysis.